(untitled) (Regional aspects of productive forces development of Ukraine, 2024)
ANNOTATION Introduction. The issues of optimizing spatial development of regions through bioeconomic approaches, which are crucial for solving contemporary global problems, including climate change, depletion of natural resources, and ensuring energy and food security are considered. Traditional approaches fail to account for ecological constraints, leading to ecosystem degradation. The integration of innovative biotechnologies, renewable resources, and environmentally responsible practices in spatial planning promotes sustainable development of territories, enhances their competitiveness, and preserves natural wealth. This allows for the creation of new economic growth points, particularly in the agroindustrial complex, energy sector, medicine, and bioproduct production, and ensures effective regional management that balances economic interests with ecological stability. The aim of the article is to investigate the preconditions and prospects of bioeconomy sector development in the region. Research Methods. The research methodology includes methods of analysis and synthesis, and systematic generalization. Results. The study analyzes the characteristics and features of the distribution of bioeconomy sector objects and bioresource supply in the territory of the Ternopil region. An evaluation of the levels of development of different bioeconomy sectors in the region’s administrative districts has been conducted. It was found that agriculture, the food industry, especially the sugar and alcohol industries, have the highest potential for innovation, particularly in waste processing and the production of bioethanol and biodiesel. It was established that the best development of the bioeconomy sector is realized in the Ternopil and Chortkiv districts, requiring intensified work in the Kremenets region. The study concludes that the overall level of bioeconomy development in the region lags behind neighboring areas. It is emphasized that the implementation of bioenergy technologies has significant ecological benefits, including the reduction of CO2 emissions and the improvement of soil quality, and is crucial for ensuring the sustainable development of the bioeconomy in the region by expanding organic fertilizer production and creating favorable conditions for investment. The article proposes directions for further development of the bioeconomy sector in the Ternopil region in the future. Keywords: bioeconomy; bioresource; spatial development; region; bioeconomy sector; agriculture.